Tetracycline resistance and presence of tetracycline resistance determinants tet(V) and tap in rapidly growing mycobacteria from agricultural soils and clinical isolates - Kyselková, Martina; Chroňáková, Alica; Volná, Lucie; Nĕmec, Jan; Ulmann, Vít; Scharfen, Josef; Elhottová, Dana (Microbes and environments, 2012)
Rapidly growing mycobacteria (RGM) inhabit soil and water but certain strains represent a health risk for human and animals. Both clinical and soil RGM may be under selection pressure for resistance to tetracycline (TET) antibiotics, since tetracyclines are administrated to humans and farm animals, and TET residues enter soil through manuring; however, resistance to TET and the presence of TET-resistance genes have been assessed only in clinical isolates. We were therefore interested in comparing soil and clinical RGM in terms of TET resistance and the presence of TET-resistance genes. We used 44 RGM from grasslands with different exposure to animal manure, and 38 clinical RGM from Czech hospitals. There was no difference between the clinical and soil isolates in TET resistance, with >50% resistant isolates in both groups. otr(A), otr(B), tet(K), tet(L) or tet(M) were not detected in any soil or clinical isolate. In contrast, most isolates harbored tet(V) and tap, both encoding mycobacterial efflux pumps, including species where these genes have never been evidenced before. The phylogeny of tet(V) correlated with isolates' BOX-PCR profiles, suggesting that this gene evolved along with mycobacterial genomes as a part of the intrinsic resistome. In certain cases, tet(V) and/or tap were found in TET-sensitive isolates, or inversely, were not found in resistant strains. Concluding, intrinsic efflux pumps may be more important for TET resistance than horizontally transferred genes in both soil and clinical RGM. Their simple presence, however, does not attest to resistance, and therefore their diversity, function and expression merit further research.
Keywords: Microbial Sensitivity Tests; DNA fingerprinting; Molecular Sequence Data; Genes, Bacterial; molekulární sekvence - údaje; DNA Fingerprinting; Tetracycline; mikrobiální testy citlivosti; RNA ribozomální 16S; rezistence na tetracyklin; antibakteriální látky; RNA, Ribosomal, 16S; biologický transport; Anti-Bacterial Agents; Mycobacteriaceae; bakteriální geny; půdní mikrobiologie; tetracyklin; Tetracycline Resistance; Biological Transport; Soil Microbiology